Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Pada PT. Sido Muncul Semarang - ., Ngatmo; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The aim of this research was to find out the infuence of variable ofproduct quality, price, service quality, emotional factor, cost and ease towards customersatisfaction. The population in this research was all customers of PT. Sido MunculSemarang. The samples were 100 customers with the technique sampling wasconvenience sampling method. The analysis tool used was multiple linear regression. Theresult of this research showed that based on hypothesis testing, it got result as big asX1=2,815, X2=2,055, X3=4,088 and X4=3,789, X5= 2,470 and t table 1,985 so that residein region refuses ho, meaning there was significant influence of product quality, price,service quality, emotional factor, cost and ease towards customer satisfaction. While inFtest, it got result Fcount 39,349 > F table (2,31) reside in region refuses ho, meaningthere was significant influence of product quality, price, service quality, emotionalfactor, cost and ease towards customer satisfaction. The determination coefficient fromthe five free variables as big as 65.9%, meaning variation from the five free variables inexplaining customer satisfaction as big as 65.9%, while the rest (100% - 65,9%) = 34,1%explained by other variables that were not mentioned in this research, for examplelocation and product completion.Keywords: product quality, price, service quality, emotional factor, cost and easetowards customer satisfaction.